PENGEMBANGAN DAN IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF: ANALISIS EFEKTIVITAS DAN DAMPAK DALAM TRANSFORMASI DIGITAL PENDIDIKAN: DEVELOPMENT AND IMPLEMENTATION OF INTERACTIVE LEARNING MEDIA: AN ANALYSIS OF EFFECTIVENESS AND IMPACT IN THE DIGITAL TRANSFORMATION OF EDUCATION - Laela, Nurlaela; Kholifah, Nurul; Nurlela (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
This research aims to examine the development and implementation of interactive learning media and their impact on digital transformation in education. The methodology used is a qualitative approach with case studies in educational institutions that have implemented interactive learning media, using data collection techniques through in-depth interviews, participatory observation, and document analysis. The theoretical foundation of this research refers to Vygotsky's constructivism theory and Mayer's cognitive theory, which emphasize the importance of interactivity in improving understanding and information retention. Research findings indicate that interactive learning media contribute positively to increasing student engagement and concept understanding through more dynamic learning experiences. However, successful implementation heavily depends on infrastructure readiness, teacher competency, and technology accessibility. This research highlights the urgency of educator training and the development of adaptive media design according to learner needs. Thus, this study provides significant contributions to developing more effective implementation strategies for interactive learning media to support digital transformation in education.